INTEROPERABILITY OF MONITORING-RELATED TOOLS - Funika, Włodzimierz; Janik, Arkadiusz (Computer Science, 2013)
Networking, distributed and grid computing have become the commonly used paradigms ofprogramming. Due to the complicated nature of distributed and grid systems and the increasing complexity of the applications designed for these architectures, the development processneeds to be supported by diﬀerent kinds of tools at every stage of a development process. Inorder to avoid improper inﬂuences of one tool to another these tools must cooperate. Thecooperation ability is called interoperability. Tools can interoperate on diﬀerent levels, fromexchanging the data in common format, to a semantical level by executing some action asa result of an event in another tool. In this paper we present some interoperability models,with focus on their advantages and major problems due to their use. We also present aninteroperability model designed and used in the JINEXT extension to OMIS speciﬁcation,intended to provide interoperability for OMIS-compliant tools.